Musealisation of the Archaeological Area of Praça Nova do Castelo de S. Jorge, Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
The Praça Nova do Castelo de São Jorge, with a privileged view over the city and the Tagus River, was the object of an extensive archaeological campaign, started in 1996, that unearthed traces of successive periods of its occupation: the first strategic se!lements of people of Iberian, Celtic or Punic origin (dating back to at least the 7th century B.C.); the Muslim occupation (witnessed by a residential quarter of the mid-11th century); and the golden age of discoveries and conquests (witnessed by fragments of the Palace of the Counts of Santiago, of the 16th-18th centuries, built on the ruins of the Episcopal palace of the 12th-15th centuries). While the most relevant artefacts were removed and exhibited at the Museological Centre of Castelo de São Jorge, the Musealization of the Archaeological Area project, which resulted from a call for tenders launched by EGEAC, a Lisbon municipal company, was carried out in order to make known, but also to protect and conserve, the excavation area.